2002
DOI: 10.1354/vp.39-4-473
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Histopathologic Features of 14 Malignant Fibrous Histiocytomas from Flat-Coated Retrievers

Abstract: Flat-Coated Retrievers seem to be at increased risk of developing soft-tissue sarcomas, and undifferentiated round cell or spindle cell sarcomas account for approximately 59% of sarcomas in the breed. In an attempt to classify these tumors further, formalin-fixed, paraffin-embedded sections from 14 undifferentiated sarcomas from Flat-Coated Retrievers were reviewed and examined with a panel of histologic and immunohistochemical stains. The panel included vimentin, desmin, Myo D1, smooth muscle actin, cytokerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
57
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 23 publications
6
57
0
1
Order By: Relevance
“…MFH has been described in dogs, cats, horses and a cow (Ford et al, 1975;Gleiser et al, 1979;Hamir 1989;Hendrick et al, 1992;Waters et al, 1994;Sartin et al, 1996;Morris et al, 2002). Findings of one report (Waters et al, 1994) indicated that MFH comprised 0.34% of all dogs evaluated for tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MFH has been described in dogs, cats, horses and a cow (Ford et al, 1975;Gleiser et al, 1979;Hamir 1989;Hendrick et al, 1992;Waters et al, 1994;Sartin et al, 1996;Morris et al, 2002). Findings of one report (Waters et al, 1994) indicated that MFH comprised 0.34% of all dogs evaluated for tumors.…”
mentioning
confidence: 99%
“…In domestic animals, three subtypes of MFH have been reported: storiform-pleomorphic, giant cell and inflammatory (Hendrick et al, 1992;Morris et al, 2002). The histogenesis of MFH is controversial, and the cell of origin is unobvious (Ford et al, 1975;Suh et al, 2000).…”
mentioning
confidence: 99%
“…At first, the chosen panel showed compatibility to the results reported in the scientific literature (Pereira et al 2000, Morris et al 2002, Mukaratirwa & Gruys 2003, Araú-jo et al 2012, Mascarenhas et al 2014. In fact, the phenotypic profile presented by the authors to identify the TVT cells can be considered as an auxiliary method in the definitive diagnosis of the tumor.…”
Section: Discussionmentioning
confidence: 53%
“…From a clinical point of view, TVT cells have been usually characterized through markers such as vimentin, lysozyme, alpha-antitrypsin (Moore & Rosin 1986, Sandusky et al 1987, Mozos et al 1996, Marchal et al 1997, Pereira et al 2000, Morris et al 2002, Mukaratirwa & Gruys, 2003, Araújo et al 2012, Mascarenhas et al 2014. For this reason, these antibodies were firstly considered to characterize TVT primary cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of lymphocytes only has been reported before in canine HS (1,6,20,24,28,39,52), but inflammatory patterns of neutrophils only (34), a combination of lymphocytes and plasma cells (25), of lymphocytes and neutrophils (7), of neutrophils and eosinophils (33), and of lymphocytes, plasma cells and neutrophils (1,26,25,51) have also been reported. The difference between BMD and FCR with regard to inflammatory pattern, with BMD having more often small lymphocytes, has not been reported before as far as we are aware.…”
Section: Discussionmentioning
confidence: 82%